OPTIMIZING HEALTH AND QUALITY OF LIFE IN CHRONIC KIDNEY DISEASE THROUGH NUTRITION: A SYSTEMATIC REVIEW - Natalia Glanc; Mateusz Myśliwiec; Tytus Tyralik; Maciej Karwat; Julia Kular; Oliwia Malec; Justyna Niebylecka; Izabella Michalska; Dominik Sendecki; Grzegorz Zalewski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Chronic kidney disease (CKD) affects over 700 million people globally and can lead to serious complications like hypertension, cardiovascular disease, and kidney failure. As CKD often progresses silently, early lifestyle changes especially dietary modification are crucial for slowing its progression.Objective: This review evaluates recent scientific evidence on the effects of various dietary interventions on clinical, metabolic, and quality-of-life outcomes in people with CKD. It focuses on low-protein diets, sodium restriction, plant-based diets, omega-3 supplementation, time-restricted feeding, ketogenic diets, and educational programs.Methods: Following PRISMA guidelines, a systematic review was conducted using PubMed, Scopus, and Web of Science for studies published from January 2020 to May 2025. Studies were included if they involved adults with CKD and tested a dietary intervention. A total of 23 studies met the criteria.Results: Low- and very-low-protein diets, particularly with ketoanalogues, were generally safe and helped delay CKD progression. Sodium restriction lowered blood pressure and preserved kidney function in early stages. Plant-based diets and fiber supplements improved metabolic markers and toxin levels without causing hyperkalemia. Emerging approaches like ketogenic and time-restricted diets showed promise in improving weight and kidney health in select patients. Educational programs significantly enhanced dietary habits and health outcomes.Conclusions: Diet is central to CKD management. Low-protein diets remain foundational, but combining them with plant-based foods, fiber, omega-3s, and structured education may offer greater benefits. Personalized, holistic dietary plans could improve outcomes and reduce dialysis risk, though more long-term studies are needed.